Therapy with 2'-O-Me Phosphorothioate Antisense Oligonucleotides Causes Reversible Proteinuria by Inhibiting Renal Protein Reabsorption - Manoe J. Janssen; Tom T.G. Nieskens; Tessa A.M. Steevels; Pedro Caetano-Pinto; Dirk den Braanker; Melissa Mulder; Yolanda Ponstein; Shaun Jones; Rosalinde Masereeuw; Cathaline den Besten; Martijn J. Wilmer (Elsevier, 2019)
Antisense oligonucleotide therapy has been reported to be associated with renal injury. Here, the mechanism of reversible proteinuria was investigated by combining clinical, pre-clinical, and in vitro data. Urine samples were obtained from Duchenne muscular dystrophy (DMD) patients treated with drisapersen, a modified 2'O-methyl phosphorothioate antisense oligonucleotide (6 mg/kg). Urine and kidney tissue samples were collected from cynomolgus monkeys (Macaca fascicularis) dosed with drisapersen (39 weeks). Cell viability and protein uptake were evaluated in vitro using human conditionally immortalized proximal tubule epithelial cells (ciPTECs). Oligonucleotide treatment in DMD patients was associated with an increase in urinary alpha-1-microglobulin (A1M), which returned to baseline following treatment interruptions. In monkeys, increased urinary A1M correlated with dose-dependent accumulation of oligonucleotide in kidney tissue without evidence of tubular damage. Furthermore, oligonucleotides accumulated in the lysosomes of ciPTECs and reduced the absorption of A1M, albumin, and receptor-associated protein, but did not affect cell viability when incubated for up to 7 days. In conclusion, phosphorothioate oligonucleotides appear to directly compete for receptor-mediated endocytosis in proximal tubules. We postulate that oligonucleotide-induced low molecular weight proteinuria in patients is therefore a transient functional change and not indicative of tubular damage. Keywords: Antisense oligonucleotide therapy, low molecular weight proteinuria, megalin, receptor-mediated endocytosis, proximal tubule epithelial cell